An Anatomy of Credit Booms : Evidence From Macro Aggregates and Micro Data - Terrones, Marco; Mendoza, Enrique (Washington, D.C. : International Monetary Fund, 2008)
We study the characteristics of credit booms in emerging and industrial economies. Macro data show a systematic relationship between credit booms and economic expansions, rising asset prices, real appreciations and widening external deficits. Micro data show a strong association between credit booms and leverage ratios, firm values, and banking fragility. We also find that credit booms are larger in emerging economies, particularly in the nontradables sector; most emerging markets crises are associated with credit booms; and credit booms in emerging economies are often preceded by large capital inflows but not by financial reforms or productivity gains.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet